The role and function of the Musi Rawas learning activities center as a non-formal unit - Hartoyo, Hartoyo; Danim, Sudarwan; Kristiawan, Muhammad (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research aims to find out and describe the current situation and the role played by the Musi Rawas Regency Learning Activities Centre through the head and administrators in building the quality of human resources in the region, existing resources, facilities owned and programs implemented as well as inhibiting and supporting factors. This research uses a qualitative approach with descriptive methods, data collection using interview, observation and documentation techniques. Meanwhile, data analysis was carried out using the interactive model from Miles and Hubermann, namely data collection, data reduction, data presentation and drawing conclusions as well as research validity using triangulation techniques. The results of the research describe the current condition of the Musi Rawas Regency Learning Activity Centre, including existing resources, which have carried out several roles with various activity programs in building the quality of human resources, including education, training, skills and community empowerment programs. Several inhibiting factors that occur are a lack of human resources, especially learning tutors, very minimal funding support from the Regional Government, social conditions in the surrounding community that are less supportive and less enthusiastic about the activities being carried out. Meanwhile, the supporting factors found include the availability of adequate supporting facilities and facilities, the existence of other local educational institutions and collaboration with various community institutions.